2015
DOI: 10.1037/bul0000009
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and motor learning: Is there room for consolidation?

Abstract: It is widely believed that sleep is critical to the consolidation of learning and memory. In some skill domains, performance has been shown to improve by 20% or more following sleep, suggesting that sleep enhances learning. However, recent work suggests that those performance gains may be driven by several factors that are unrelated to sleep consolidation, inviting a reconsideration of sleep's theoretical role in the consolidation of procedural memories. Here we report the first comprehensive investigation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
222
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(230 citation statements)
references
References 74 publications
8
222
0
Order By: Relevance
“…Minutes in rapid eye movement (REM) sleep, on the other hand, are associated with improvements in implicit memory [e.g., unconscious, priming, procedural skills (4,5)]. However, recent reviews and meta-analyses of the literature report inconsistencies in these findings (6,7), suggesting that there may be unexplored factors critical to sleep-dependent memory consolidation.…”
mentioning
confidence: 94%
“…Minutes in rapid eye movement (REM) sleep, on the other hand, are associated with improvements in implicit memory [e.g., unconscious, priming, procedural skills (4,5)]. However, recent reviews and meta-analyses of the literature report inconsistencies in these findings (6,7), suggesting that there may be unexplored factors critical to sleep-dependent memory consolidation.…”
mentioning
confidence: 94%
“…In several studies, researchers have identified a number of moderating variables that may account for at least a portion of the performance improvement following sleep (see Pan and Rickard, 2015, for a comprehensive review and meta-analysis). Some of these data even suggest that under some circumstances, skill performance after sleep may not be better than after a period of wakefulness (e.g., Backhaus et al, 2016), inviting a reconsideration of sleep’s theoretical role in the consolidation of procedural memories (Nettersheim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is critical for learning and memory consolidation38. For declarative memory, slow wave sleep has a beneficial effect on the consolidation of memories acquired during preceding wakefulness338.…”
Section: Discussionmentioning
confidence: 99%
“…For declarative memory, slow wave sleep has a beneficial effect on the consolidation of memories acquired during preceding wakefulness338. Sleep/wake cycles are controlled by the super chiasmic nucleus in the hypothalamus, but can be disrupted by diseases of the nervous system, causing sleep disorders.…”
Section: Discussionmentioning
confidence: 99%